2004
DOI: 10.1164/rccm.200302-265oc
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep-disordered Breathing and Sleep Apnea in Middle-aged Urban Indian Men

Abstract: No data are available on the prevalence of sleep-disordered breathing (SDB) and obstructive sleep apnea-hypopnea syndrome (OSAHS) in Indians. We conducted a two-phase cross-sectional prevalence study for the same in healthy urban Indian males (35-65 years) coming to our hospital in Bombay for a routine health check. We also investigated its risk factors and evaluated the significance of the most commonly asked questions that best correlated with the presence of OSAHS. In the first phase, 658 subjects (94%) ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
215
6
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(246 citation statements)
references
References 43 publications
18
215
6
7
Order By: Relevance
“…Udwadia and colleagues demonstrated in their study that although an association of SDB with hypertension was significant, multiple logistic regression analysis did not select hypertension as a principle covariate. 25 However, a high prevalence of hypertension in sleep apnoea has been unequivocally demonstrated in the present study as well as other studies [19][20][21] and emphasises the role of early diagnosis and treatment of sleep apnoea patients as well as the importance of evaluating all the newly diagnosed sleep apnoeic patients for hypertension.…”
Section: -21supporting
confidence: 76%
“…Udwadia and colleagues demonstrated in their study that although an association of SDB with hypertension was significant, multiple logistic regression analysis did not select hypertension as a principle covariate. 25 However, a high prevalence of hypertension in sleep apnoea has been unequivocally demonstrated in the present study as well as other studies [19][20][21] and emphasises the role of early diagnosis and treatment of sleep apnoea patients as well as the importance of evaluating all the newly diagnosed sleep apnoeic patients for hypertension.…”
Section: -21supporting
confidence: 76%
“…This signifies that approximately 5 -10 million Americans are affected. In India Udwadia et al 12 reported that the estimated prevalence of sleep disordered breathing was 19.5% and that of obstructive sleep apnea hypopnea syndrome ( SDB and daytime hypersomnolence) was 7.5%. Further, snoring can be observed when a group of subjects are sleep together as for example in railway sleeper coaches .…”
Section: Sleep Disordersmentioning
confidence: 99%
“…(10) The definition of OSAS is an apnea-hypopnea index (AHI) above five events per hour of sleep, together with excessive daytime sleepiness. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) A recent epidemiological study conducted in the city of São Paulo, Brazil, (11) showed a high prevalence of OSAS in the adult population (32.8%). (12) In that study, OSAS was defined according to the criteria of the most recent International Classification of Sleep Disorders, published by the American Academy of Sleep Medicine (AASM) in 2005, (13) which state that a diagnosis of OSAS can be confirmed if the subject has an AHI of 5.0-14.9 events per hour of sleep and presents with at least one of the following complaints: loud snoring, excessive daytime sleepiness, and fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea syndrome (OSAS) is a highly prevalent condition that is observed in 1.2% to 7.5% of the general population, (1)(2)(3)(4)(5)(6)(7)(8)(9) mostly in adults and primarily in obese males. (10) The definition of OSAS is an apnea-hypopnea index (AHI) above five events per hour of sleep, together with excessive daytime sleepiness.…”
Section: Introductionmentioning
confidence: 99%